The Canis tangle: a systematics overview and taxonomic recommendations - V. Dinets (Вавиловский журнал генетики и селекции, 2015)
Despite high research interest, the systematics and taxonomy of mammalian genus Canis are among the most convoluted and controversial: species boundaries are blurred and incongruent with any existing species concept, while genetic differences between species are low. I provide an overview of existing controversies, the most recent findings, and taxonomic possibilities, and recommend the most practical and well-substantiated solutions. The genus boundaries have to be changed, with two African jackals (C. adustus & C. mesomelas) moved to a separate genus Lupulella. The systematic status of taxa occurring in eastern North America has caused much argument; most recent data indicate that Algonquin (C. lycaon lycaon) and Red (C. l rufus and recently exterminated subspecies) Wolves originate from ancient hybridization and should be considered a separate species, while two other populations are of more recent hybrid origin. The systematic position, intraspecific classification, origin and taxonomy of Dog (C. familiaris) are particularly controversial. It has been alternatively classified as a subspecies of Gray Wolf (C.lupus), a subspecies of Dingo (C. dingo), or a full species (C. familiaris) with Dingo as a subspecies. Analysis of available data shows that Dog should be classified as a full species with four subspecies, since its origin from a common ancestor with modern Gray Wolf has likely predated its domestication (contrary to the most popular view), and interbreeding between Dog and Gray Wolf in the wild is limited. It is possible that never-domesticated Dog populations have survived in southeastern Asia until very recently, or even exist today.